ORGANISATIONAL POLITICS: THE POSITIVE & NEGATIVE SIDES - Cacciattolo, Karen (European Scientific Journal, ESJ, 2015)
There are two ways of viewing organisational politics: either as a symptom of social influence processes that benefit the organisation, or a self serving effect that goes against the organisational goals (Mintzberg, 1985: 148; Gotsis & Kortezi, 2010: 498). Nevertheless, the concept of organisational politics is a key social influence process that can be either functional or dysfunctional to employees and organisations (Allen et al, 1979: 82). Organisational politics, as argued by various researchers, can be either positive or negative (Othman, 2008: 44) and this paper delves into both sides of the organisational politics by offering examples from literature and research carried out throughout the years.